Differential proteomic analysis of endemic and sporadic Epstein–Barr virus-positive and negative Burkitt lymphoma. Issue 1 (January 2015) - El-Mallawany, Nader Kim; Day, Nancy; Ayello, Janet; Van de Ven, Carmella; Conlon, Kevin; Fermin, Damian; Basrur, Venkatesha; Elenitoba-Johnson, Kojo; Lim, Megan; Cairo, Mitchell S.
Abstract Background Burkitt lymphoma (BL) is the most common non-Hodgkin lymphoma in children worldwide and the most common paediatric malignancy in sub-Saharan Africa. The endemic (eBL) and sporadic (sBL) variants have distinct epidemiologic and virologic characteristics. Although gene expression studies have defined the transcriptional profiles of both, their proteomic signatures have not been studied. Methods We compared the proteomic expression profiles using differential mass spectrometry-based isotope tag for relative and absolute quantitation (iTRAQ) analysis of a cell line representing Epstein–Barr virus (EBV)+ eBL, EBV+ and EBV– sBL, and EBV+/– normal B cells from healthy donors. Results In total, there were 144 differentially expressed proteins with a statistically significant false discovery rate (FDR) of ⩽0.2. Results revealed over-expression of specific proteins with well-established links to lymphomagenesis such as TUBB2C (FDR 0.05), UCHL1 (FDR 0.05) and HSP90AB1 (FDR 0.1). Distinct characteristics based upon the epidemiologic and virologic subtypes of BL were also identified. In sBL, PCNA (FDR 0.05) and SLC3A2 (FDR 0.1) were significantly over-expressed. In eBL, C1QBP (FDR 0.1) and ENO1 (FDR 0.25) were significantly over-expressed. Comparison of EBV+ to EBV– BL cell lines and B cells revealed significant over-expression of DDX3X (FDR 0.1). Proteins were validated using Western blot analysis. Conclusion Our results suggest unique signal transduction pathways associated with EBV infection and epidemiological subtype of BL that may contribute to lymphomagenesis. These proteomic findings provide potential diagnostic, prognostic and therapeutic links to BL.